Laparoscopic esophagomyotomy for achalasia without a complementary antireflux procedure. - Diamantis, Theodoros; Pikoulis, Emmanouil; Felekouras, Evangelos; Tsigris, Christos; Arvelakis, Antonios; Karavokyros, Ioannis; Bastounis, Elias (J Laparoendosc Adv Surg Tech A, 2006)
BACKGROUND: Achalasia is a progressive motility disorder of the esophagus, without a definitive cure. The principal method of palliation is myotomy of the distal esophagus. We analyzed the 5-year experience at our institution with laparoscopic Heller myotomy without an antireflux procedure to determine its results, particularly regarding postoperative gastroesophageal reflux. MATERIALS AND METHODS: Thirty-three patients, mean age 43 years (range, 29-62 years) with clinical, manometric, x-ray, and endoscopic proof of achalasia were operated on and followed up for 24 months. Prior to being referred to surgery they had all undergone at least one pneumatic balloon dilation. The operative technique was a 7-cm myotomy that included the lower esophageal sphincter but did not exceed 5 mm of the gastric cardia. Follow-up consisted of clinical observation, cineesophagography, and 24-hour pHmetry. RESULTS: All patients reported satisfactory to excellent results regarding dysphagia and no heartburn two years after the operation. The 24-hour pHmetry and the radiographic investigation showed no evidence of gastroesophageal reflux. CONCLUSION: It seems that the risk of gastroesophageal reflux is very low when the cardiomyotomy does not exceed the length of 5 mm. Our results are in accordance with other observational studies as well as larger cohort and meta-analysis studies. Prospective randomized studies are needed to clarify the role of an antireflux procedure after laparoscopic Heller myotomy.
Keywords: Adult; Cardia; Catheterization; Deglutition Disorders; Esophageal Achalasia; Esophageal pH Monitoring; Esophageal Sphincter, Lower; Esophagectomy; Female; Follow-Up Studies; Gastroesophageal Reflux; Humans; Laparoscopy; Male; Middle Aged; Patient Satisfaction; Treatment Outcome